Chlorido(chloro-difluoro-acetato-κO)bis(1,10-phenanthroline-κN,N')manganese(II). - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2008)
The chloride and chloro-difluoro-acetate anions occupy cis positions in the octa-hedral coordination geometry of the title compound, [Mn(C(2)ClF(2)O(2))Cl(C(12)H(8)N(2))(2)]. The two N-heterocycles both chelate the metal atom.